Effect of an educational intervention on the breastfeeding technique on the prevalence of exclusive breastfeeding - Tâmara Oliveira de Souza; Thaize Estrela do Vale Morais; Camilla da Cruz Martins; José de Bessa Júnior; Graciete Oliveira Vieira (Revista Brasileira de Saúde Materno Infantil, 2020)
Abstract Objectives: to evaluate the effect of an intervention directed to the breastfeeding technique in the prevalence of exclusive breastfeeding in the first month of life. Methods: this is a quasi-randomized intervention study conducted in a public maternity ward accredited in the Baby-Friendly Hospital Initiative. The intervention consisted of individual orientations on the breastfeeding technique in the first 48 hours after delivery, with the help of a breast model, doll, and movie. The control group was oriented by researchers about the importance of breastfeeding, and received hospital orientations. Data were collected in the maternity ward, and at the end of the first month in the hospital’s outpatient service by implementing a questionnaire, observing the baby’s breastfeeding technique and examining breasts. Results: the prevalence of exclusive breastfeeding in the first month of life of the infant was 76.6% in the experimental group, and 52.2% in the control group. RR=1.46 (CI95%=1.16-1.84); NNT=4.09; p=0.001. The trained women presented a correct breast-feeding technique in 64.04%, much higher when compared to those who did not receive training (15.11%;RR=4.87[CI95%=2.93-8.34]; NNT=1.96;p<0.001). Conclusions: the use of audiovisual resources, use of instruments (model breast and doll), and type of individualized approach contributed to an increased prevalence of exclusive breastfeeding up to 30 days after delivery.